2020
DOI: 10.13057/biodiv/d210145
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of medicinal plants utilized by To Manui ethnic of Central Sulawesi, Indonesia

Abstract: Abstract. Rahmawati N, Mustofa FI, Haryanti S. 2020. Diversity of medicinal plants utilized by To Manui ethnic of Central Sulawesi, Indonesia. Biodiversitas 21: 375-392. The present study reports the utilization of medicinal plants as medicines for the treatment of various diseases among the people of To Manui tribe in Central Sulawesi Province of Indonesia. Data collecting was conducted based on purposive random sampling to five selected traditional healers who fulfilled some inclusion criteria. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
10
0
3
Order By: Relevance
“…In general, the knowledge of the residents about medicinal plants was limited to the use of plants for common diseases such as skin diseases, digestive system, respiratory system, and parasitic diseases. These findings have several similarities with other studies conducted in various regions in Indonesia (Silalahi et al 2015;Malini et al 2017;Indriwati and Suhadi 2018;Rahmawati et al 2020) Urban park plants that were used by the residents as vegetables were C. papaya, Cnidoscolus aconitifolius, C. sulphureus, and M. utilissima. The leaves of these plants were used for vegetables.…”
Section: Plant Function Perceived By the Residentssupporting
confidence: 87%
See 1 more Smart Citation
“…In general, the knowledge of the residents about medicinal plants was limited to the use of plants for common diseases such as skin diseases, digestive system, respiratory system, and parasitic diseases. These findings have several similarities with other studies conducted in various regions in Indonesia (Silalahi et al 2015;Malini et al 2017;Indriwati and Suhadi 2018;Rahmawati et al 2020) Urban park plants that were used by the residents as vegetables were C. papaya, Cnidoscolus aconitifolius, C. sulphureus, and M. utilissima. The leaves of these plants were used for vegetables.…”
Section: Plant Function Perceived By the Residentssupporting
confidence: 87%
“…Some studies regarding urban parks were undertaken by some scholars in several themes, including microclimate assessment in the chosen localities of Nitra, Slovakia (Rózová et al 2020), assessment of toxic effect on plant, risk of environmental and health on the urban park soils (Brtnický et al 2019), the influence of urban park on the temperature of local urban environment (Yan et al 2018), composition and structure of vegetation of urban parks in different countries (Zhao et al 2010;Pearse et al 2018;Talal and Santelmann 2019), the relationship between vegetation and ecological functions, such as microclimate and carbon sinks (Cundaningsih et al 2015;Erdianto et al 2019), and perception and knowledge of plant diversity related to urban park management (Muratet et al 2015;Talal and Santelmann 2020). In more details, some studies looked at the particular uses of the plants cultivated in urban park including for traditional medicine (Taek et al 2019;Rahmawati et al 2020), ornamental plants (Lacy and Shackleton 2017), edible fruits (Lacy and Shackleton 2017), religious ceremonies (Dash et al 2019;Sujarwo et al 2020;Sutrisno et al 2020), timber and fuelwood (Nagendra and Gopal 2010), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Rohman et al [24] reported that the Tengger tribe located in Bromo Tengger Semeru National Park, East Java utilized C. odorata as an insect repellent. Rahmawati et al [25] mentioned this species utilized by To Manui ethnic of Central Sulawesi, Indonesia as a flu healer.…”
Section: Species Richness and Abundance Of Medicinal Plantsmentioning
confidence: 99%
“…), and calabura (Muntingia calabura L) to treat diabetes and high blood pressure. Medicinal plants are a vital source to combat human diseases and play an essential role in healing many serious diseases worldwide due to active phytochemical compounds (Rahmawati et al 2020). According to Islam and Sarwar (2020), Terminalia arjuna (Roxb.)…”
Section: Medicinal Plantsmentioning
confidence: 99%
“…Parts of plants commonly used as medicines include leaves, stems, roots, and rhizomes. Leaf, root, bark, herbaceous parts, and seed are the five highest utilization parts of plants (Rahmawati et al 2020;Karthiyayini 2012;Town 2018).…”
Section: Medicinal Plantsmentioning
confidence: 99%